Effects of Silica Nanoparticles and Silica-Zirconia Nanoclusters on Tribological Properties of Dental Resin Composites - Henry A. Rodríguez; Herley Casanova (Journal of Nanotechnology)
Roughness and hardness are among the most important variables in the wear (resistance) performance of dental resin composites. In this study, silica nanoparticles and nanoclusters of silica and silica-zirconia nanoparticles were evaluated for use as reinforcement agents in dental resin composites. Nanoclusters with spherical morphology were obtained from aqueous dispersions of nanoparticles by spray drying. Roughness was measured through atomic force microscopy (AFM) while nanohardness was evaluated by nanoindentation. The roughness values obtained with silica nanoparticles were lower (22.6 ± 6.6 nm) than those obtained with silica and silica-zirconia nanoclusters (138.1 ± 36.6 nm, 116.2 ± 32.2 nm, resp.), while the hardness values of all composites were similar (nanoparticles = 0.24 ± 0.01 GPa, silica nanoclusters = 0.25 ± 0.04 GPa, and silica-zirconia nanoclusters = 0.22 ± 0.02 GPa). Based on this study, it can be established that particle size is a determining factor in the roughness of the final material, while the key variable for nanohardness was the concentration of the reinforcement materials.